2011
DOI: 10.1002/cncy.20192
|View full text |Cite
|
Sign up to set email alerts
|

The atypia of undetermined significance/follicular lesion of undetermined significance:malignant ratio

Abstract: BACKGROUND:The Bethesda System (TBS) for reporting thyroid cytopathology introduced the atypia of undetermined significance/follicular lesion of undetermined significance (AUS) category, but did not provide adequate guidance for the appropriate use of this diagnosis. In the current study, the authors sought to identify an appropriate measure for AUS use based on experience to date with TBS.METHODS:The authors reviewed 8 series, including their own laboratory experiences, with a total of 30,466 thyroid aspirate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
60
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 125 publications
(65 citation statements)
references
References 15 publications
(53 reference statements)
5
60
0
Order By: Relevance
“…This is because the parallels between indeterminate diagnoses in gynecological cytopathology and thyroid cytopathology are few and tenuous. For example, the ASC/SIL ratio that is useful in gynecological cytopathology is difficult to modify for the thyroid, even though some attempts have been made [20]. One of the key differences between gynecological and thyroid malignancy is the diversity of cell types and disease processes in the thyroid.…”
Section: Discussionmentioning
confidence: 99%
“…This is because the parallels between indeterminate diagnoses in gynecological cytopathology and thyroid cytopathology are few and tenuous. For example, the ASC/SIL ratio that is useful in gynecological cytopathology is difficult to modify for the thyroid, even though some attempts have been made [20]. One of the key differences between gynecological and thyroid malignancy is the diversity of cell types and disease processes in the thyroid.…”
Section: Discussionmentioning
confidence: 99%
“…The Bethesda System cytopathologic description of the AUS/FLUS category consists of 9 different criteria including the heterogeneous histology results with a wide range of risk of malignancy [1,10,11,12,13,14]. Several studies have attempted to divide the AUS/FLUS category into the subcategories AUS and FLUS [10,11,12,13,14]. Recently, Choi et al [21 ]reported that the AUS subcategory displayed a higher risk of malignancy when using core-needle biopsy specimens.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Bethesda System for Reporting Thyroid Cytopathology, the category follicular lesion of undetermined significance (FLUS)/atypia with undetermined significance (AUS) includes cases which do not have convincing evidence of benignity or sufficient features in order to conclude that they are follicular neoplasms or suspicious for malignancy [1]. Recently, several studies have attempted to subclassify the AUS/FLUS category into cases with AUS and cases with FLUS [10,11,12,13,14]. AUS refers to a true nuclear atypia with a higher risk of papillary thyroid cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In TBSRTC, a target utilization rate for the AUS category was set at approximately 7% of thyroid aspirates, a figure based on the observed AUS rates from two large studies published around the time of the 2007 NCI conference [3,4], although it was acknowledged that this figure might be revisited. To date, the majority of laboratories that have retrospectively examined their experience with AUS in TBSRTC framework report rates higher than the 7% target, with a range of 2.1–18% [5,6,7,8,9,10,11,12,13,14,15]. It is not well understood what factors contribute to this variable usage by cytopathologists.…”
Section: Introductionmentioning
confidence: 99%